Doing cultural theory - Walton, David, 1955- (Los Angeles : Sage, 2012)
"Doing Cultural Theory is a textbook and a toolkit that teaches the basics of cultural theory, unpacks its complexities with real-life examples, and shows readers how to link theory and practice. Offers accessible introductions to how cultural studies has engaged with key theories in structuralism, poststructuralism and postmodernism. Teaches straightforward ways of practicing these theories so students learn to think for themselves. Uses 'Practice' boxes to show students how to apply cultural theory in the real world. Guides students through the literature with carefully selected further reading recommendations Other textbooks only show how others have analyzed and interpreted the world. Doing Cultural Theory takes it a step further and teaches students step-by-step how to do cultural theory for themselves." -- Publisher's website.
Cultural Studies: A Brief Contextual History -- Structuralism and the Linguistic Turn: Ferdinand de Saussure -- Semiotics: Umberto Eco, Roland Barthes and Stuart Hall -- Ideology: Marxism and Louis Althusser -- Post-Structuralism: Roland Barthes and Jacques Derrida -- Doing Deconstruction: Techniques for Practice -- Psychoanalysis: Jacques Lacan -- Applying Lacan: Techniques for Feminist and other forms of Cultural Analysis -- Discourse and Power: Michel Foucault -- Gender and Sexuality: Judith Butler -- The Postmodern Condition: Daniel Bell, Jean-François Lyotard and Jürgen Habermas -- Identity and Consumption: Jean Baudrillard -- Postmodernism Unplugged: Fredric Jameson -- Practising Cultural Studies: Hegemony and Cognitive Mapping -- Where to Go from Here: Cognitive Mapping and the Critical Project of Cultural Studies.
Includes bibliographical references (pages [314]-328) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Culture -- Philosophy; Culture -- Study and teaching -- Great Britain; Culture -- Study and teaching; Popular culture -- Study and teaching -- Great Britain; Popular culture -- Study and teaching; Electronic books